Magnetic carbon material for efficiently removing degradable micro-plastics in sewage and preparation of magnetic carbon material

By preparing magnetic biochar adsorbent, the mixing of FeCl2·4H2O and FeCl3·6H2O, the treatment of biochar and NaOH, and the high-temperature pyrolysis process, the problem of low removal efficiency of microplastics in wastewater is solved, efficient removal and magnetic separation are achieved, and the process is environmentally friendly and cost-effective.

CN119838566APending Publication Date: 2025-04-18ZHENGZHOU UNIV

Patent Information

Application Number
CN202510211564.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art has low removal efficiency in sewage, poor adsorption capacity of conventional adsorbents and difficult to recover. Advanced oxidation processes cannot completely degrade microplastics, but may increase the abundance of effluent microplastics.

Method used

Using magnetic carbon material, a magnetic biochar adsorbent with high adsorption removal performance was prepared by mixing FeCl2·4H2O and FeCl3·6H2O, biochar and NaOH were added, pH value was adjusted, and pyrolysis was performed at high temperature.

Benefits of technology

It realizes efficient removal of degradable microplastics in wastewater, with a removal rate of more than 80%. The adsorbent is super paramagnetic, easy to magnetic separation, and has low raw materials, simple process and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838566A_ABST
    Figure CN119838566A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sewage treatment, in particular to a magnetic carbon material for efficiently removing degradable micro-plastics in sewage and a preparation method thereof.The magnetic carbon material is characterized in that S1, FeCl2. 4H2O and FeCl3. 6H2O are evenly mixed according to the mass percent of (3-7): (2-6), and the obtained mixture is marked as A; s2, preparing a premix B; s3, obtaining a mixture C; s4, obtaining a mixture D; s5, obtaining a powder substance E; s6, completing preparation of the magnetic biochar adsorbent which has high adsorption removal performance and is easy to separate and recycle the micro-plastics. According to the magnetic carbon material for efficiently removing the degradable micro-plastics in the sewage and the preparation method of the magnetic carbon material, the biochar prepared from the waste straws in the agricultural production process is used as the raw material, and compared with adsorbents such as organic silicon materials and polyamide fibers, the used raw materials are low in cost and easy to obtain, the process is simple, and the requirements for a production line and equipment are low; meanwhile, the invention also has the effect of recycling wastes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The patent of this invention relates to the field of sewage treatment technology, specifically to magnetic carbon materials and their preparation for efficient removal of degradable microplastics in sewage. Background Art

[0002] The technologies used to remove microplastics mainly include adsorption, coagulation, membrane bioreactors and advanced oxidation processes. For example, the adsorption method uses biochar-based, sponge-based and metal-based adsorbents, and uses the affinity of the adsorbent surface to interact chemically or physically with microplastics, adsorbing them on the surface for removal. The coagulation method uses coagulants to electrically neutralize pollutants and biofilms on the surface of microplastics to form aggregates, and removes microplastics in the form of precipitation. In the membrane bioreactor method, bacterial biofilms gather microplastic particles together through their sticky properties, and disperse the biofilms through specific genes, thereby releasing microplastic particles. Advanced oxidation processes use oxidants such as persulfate and hydrogen peroxide, and activate them through light, heat, metal ions, etc. to produce active species with strong oxidizing ability, thereby achieving the degradation and removal of microplastics. Develop an adsorbent with cheap and easily available raw materials, easy to implement, no high requirements for site and equipment, high adsorption and removal performance for microplastics, and easy separation and recovery, to solve the problem of poor adsorption capacity and difficult recovery of conventional adsorbents in the adsorption method.

[0003] In the existing technology, the coagulation process usually only transfers microplastics in sewage to the remaining sludge, and cannot fundamentally solve the pollution problem; the membrane bioreactor is based on physical filtration to intercept microplastics, and its removal efficiency is high, but the membrane components are expensive and easy to clog and pollute; conventional advanced oxidation processes, such as ozone oxidation, cannot completely degrade microplastics, but may cause larger microplastics to split into several small plastic particles in the reactor, resulting in an increase in the abundance of microplastics in the effluent. Compared with other technologies, adsorption technology is low-cost and easy to implement, but the adsorbent biochar itself has limited adsorption capacity for microplastics, and it is difficult to separate it from sewage sludge after adsorption. Therefore, magnetic carbon materials and their preparation for efficient removal of degradable microplastics in sewage are urgently needed to improve the above problems.

[0004] Invention patent content

[0005] The purpose of the present invention is to solve at least one of the above technical defects.

[0006] To this end, one purpose of the present patent is to propose a magnetic carbon material and its preparation for efficient removal of degradable microplastics in sewage, so as to solve the problems mentioned in the background technology and overcome the shortcomings in the prior art.

[0007] In order to achieve the above-mentioned purpose, an embodiment of the present invention provides a magnetic carbon material for efficient removal of degradable microplastics in sewage and its preparation, comprising the following steps:

[0008] S1. Mix uniformly according to the mass percentage of FeCl_2·4H_2O:FeCl_3·6H_2O=(3-7):(2-6), and the obtained mixture is recorded as A;

[0009] S2. The mixture A obtained in the first step is stirred evenly with water to prepare a premix B;

[0010] S3. Add 2 to 6 g of biochar to the premix B and stir for 15 to 45 min to mix them evenly. The resulting mixture is recorded as C.

[0011] S4. Add NaOH with a concentration of 3 to 7 mol / L to the mixture C, adjust the pH thereof to 8 to 11, stir for 15 to 45 min to mix evenly, and the resulting mixture is recorded as D;

[0012] S5. The mixture D is allowed to stand for 18 to 26 hours, filtered, and dried at 65 to 120° C. The powder obtained after grinding through a sieve is recorded as E;

[0013] S6. Powdered substance E is pyrolyzed at 300-500° C. for 2-5 h using a tubular furnace to obtain the magnetic biochar adsorbent prepared by the present invention, which has high adsorption and removal performance and is easy to separate and recover microplastics.

[0014] The patent of the present invention is further configured as follows: in the step S1, FeCl2 is ferrous chloride, 4H2O is ammonium molybdate tetrahydrate, FeCl3 is ferric chloride, and 6H2O is magnesium chloride hexahydrate, and the mixture is added to the interior of the experimental vessel in a mass percentage of FeCl2·4H2O:FeCl3·6H2O=(3~7):(2~6), and mixed evenly to obtain a mixture A.

[0015] The present invention is further configured as follows: the mixing ratio of the mixture A and water in step S2 is: A=(8-12):1, water is added to the interior of the mixing vessel, and is fully mixed with the mixture A to obtain the premix B.

[0016] By adopting the above technical solution, water is added to the interior of the mixing vessel and fully mixed with the mixture A, thereby facilitating the dilution of the mixture A.

[0017] The patent of the present invention is further configured as follows: the biochar in step S3 can be selected from straw biochar with a mesh size of 80 to 150 meshes, the stirring intensity during mixing is 380 to 580 r / min, and after the premix B and the biochar are evenly mixed, a mixture C can be obtained.

[0018] By adopting the above technical solution, the biochar in step S3 can be selected from straw biochar with a mesh size of 80 to 150 meshes, which can facilitate mixing into the premix B.

[0019] The patent of the present invention is further set as follows: the straw biochar preparation process is: after the crops are harvested, the crop straw should be collected as soon as possible, and the collected straw should be pretreated by high-temperature combustion, chemical treatment and other methods. After the pretreated straw is burned at high temperature, the remaining part is chemically treated to form biochar with specific structure and properties.

[0020] The patent of the present invention is further configured as follows: in step S4, NaOH is sodium hydroxide, and when adding NaOH, a peristaltic pump is required to be used to add it dropwise, and the stirring intensity during mixing is 280 to 480 r / min. After NaOH is mixed with mixture C, mixture D can be obtained.

[0021] By adopting the above technical solution, when adding NaOH, a peristaltic pump needs to be used to add it drop by drop, so as to achieve the effect of accurately adding NaOH.

[0022] The present invention is further configured as follows: in step S5, after the mixture D is allowed to stand and is filtered, it is dried and ground and sieved by staff, the mesh number of the sieve is 30 to 60 meshes, and the powdery substance after the sieve is recorded as E.

[0023] By adopting the above technical solution, the mesh number of the sieve is 30 to 60 meshes, which facilitates the screening of the powdery substance E.

[0024] The patent of the present invention is further configured as follows: when the step S6 uses a tubular furnace, pyrolysis is performed in a N2 atmosphere, N2 is nitrogen, which is a single substance formed by the nitrogen element. It is a colorless and odorless gas at room temperature and pressure. It can only react with hydrogen to generate ammonia under high temperature, high pressure and catalyst conditions.

[0025] By adopting the above technical solution, step S6 uses a tubular furnace to perform pyrolysis under a N2 atmosphere, which facilitates the replacement of biogas.

[0026] The patent of the present invention is further configured as follows: the pyrolysis temperature of the tubular furnace in step S6 is 300-500°C, and the pyrolysis time is 2-5h.

[0027] In summary, the beneficial technical effects of the present invention are:

[0028] 1. The magnetic carbon material for efficient removal of degradable microplastics in sewage and its preparation method. The present invention uses biochar made from waste straw in the agricultural production process as raw material. Compared with adsorbents such as silicone materials and polyamide fibers, the raw materials used in the present invention are low in cost, easy to obtain, simple in process, and have low requirements for production lines and equipment. At the same time, the present invention also has the effect of waste recycling. The magnetic biochar adsorbent prepared by the present invention is made of agricultural waste, which not only reduces the discharge of waste, but also utilizes waste resources. No secondary pollution is generated during the preparation and use process and it can be recovered by heat treatment, which further proves its environmental friendliness.

[0029] 2. The magnetic carbon material for efficient removal of degradable microplastics in sewage and its preparation. The adsorbent prepared by the present invention has a specific surface area of ​​more than 500m2 / g, a high adsorption and removal capacity for microplastics, and a high removal and adsorption efficiency. After adding the magnetic biochar prepared by the present invention to a mixed solution of degradable microplastics with a concentration of 85-115mg / L, the removal rate is greater than 80%, and the removal efficiency is good. The adsorbent prepared by the present invention has a large magnetism. By using a vibrating sample magnetometer to analyze its magnetism, the saturation magnetization value exceeds 30emu / g and there is no residual magnetism and coercive force, indicating that it has superparamagnetism, ensuring effective magnetic separation performance, thereby achieving the purpose of separation from water;

[0030] 3. The magnetic carbon material for efficient removal of degradable microplastics in sewage and its preparation. The present invention is the first to apply magnetic biochar to the adsorption and removal of small-sized (<2μm) degradable microplastics (PBS) in sewage, revealing the adsorption and removal performance and adsorption mechanism of magnetic biochar for small-sized degradable microplastics. The research results provide a theoretical basis for linking the pollution of degradable microplastics. The raw materials used in the magnetic biochar adsorbent prepared by the present invention are taken from waste straw, which is cheap and easy to obtain, effectively reducing the production cost, thereby greatly improving the market competitiveness of the product, and at the same time strengthening the ecological environment management of microplastics, ensuring the ecological health of the water environment, and thus helping to achieve the goal of new pollutant control.

[0031] Additional aspects and advantages of the present invention will be given in part in the following description and in part will become apparent from the following description or will be learned through the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0033] Figure 1 This is the BET diagram of the patented magnetic biochar adsorbent of the present invention;

[0034] Figure 2This is the FTIR graph of the patented magnetic biochar adsorbent of the present invention;

[0035] Figure 3 This is the SEM-EDS image of the patented magnetic biochar adsorbent of the present invention;

[0036] Figure 4 This is the XRD diagram of the patented magnetic biochar adsorbent of the present invention. DETAILED DESCRIPTION

[0037] The following will clearly and completely describe the technical solutions in the embodiments of the patent of the present invention in conjunction with the drawings in the embodiments of the patent of the present invention. Obviously, the described embodiments are only part of the embodiments of the patent of the present invention, not all of the embodiments. Based on the embodiments in the patent of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the patent of the present invention.

[0038] Embodiment 1

[0039] The magnetic carbon material for efficient removal of degradable microplastics in sewage disclosed in the present invention and its preparation method include the following steps:

[0040] S1. Mix uniformly according to the mass percentage of FeCl2·4H2O:FeCl3·6H2O=(3-7):(2-6), and the resulting mixture is recorded as A;

[0041] S2. The mixture A obtained in the first step is mixed with water in a mass ratio of water: A = (8 to 12): 1 to prepare a premix B;

[0042] S3. Add 2 to 6 g of straw biochar with a mesh size of 80 to 150 mesh to the premix B, stir at a stirring intensity of 380 to 580 r / min for 15 to 45 minutes to mix evenly, and the resulting mixture is recorded as C;

[0043] S4. Add 3-7 mol / L NaOH dropwise to the mixture C using a peristaltic pump, adjust the pH to 8-11, stir at a stirring intensity of 280-480 r / min for 15-45 min to mix evenly, and the resulting mixture is recorded as D;

[0044] S5. The mixture D is allowed to stand for 18 to 26 hours, filtered, dried at 65 to 120°C, and ground through a 30 to 60 mesh sieve to obtain a powdery substance, which is recorded as E;

[0045] S6. The powdered substance E is pyrolyzed at 300-500° C. for 2-5 h in a tubular furnace with a nitrogen atmosphere to obtain the magnetic biochar adsorbent prepared by the present invention, which has high adsorption and removal performance and is easy to separate and recover microplastics.

[0046] The obtained magnetic biochar was added to 85-115 mg / L PBS and placed in a constant temperature shaker for adsorption for 18-26 hours. Then, a magnet was used for batch adsorption, the absorbance of the remaining solution was measured, the concentration of PBS was determined according to the standard curve, and the mass of PBS on the adsorbent was calculated. After calculation, the removal efficiency exceeded 80%.

[0047] In step S1, FeCl2 is ferrous chloride, 4H2O is ammonium molybdate tetrahydrate, FeCl3 is ferric chloride, and 6H2O is magnesium chloride hexahydrate. The mass percentages of FeCl2·4H2O:FeCl3·6H2O=(3~7):(2~6) are added to the interior of the experimental vessel and mixed evenly to obtain a mixture A. In this embodiment, FeCl2 shortens the water treatment cycle and reduces the water treatment cost, FeCl3 adjusts the pH value, removes pollutants and inhibits bacterial growth, and 6H2O promotes the denitrification and dephosphorization processes in the sewage treatment system and improves the treatment efficiency.

[0048] Step S2: The mixing ratio of mixture A and water is: A=(8-12):1. Water is added into the mixing vessel and fully mixed with mixture A to obtain premix B. In this embodiment, water plays the role of diluting mixture A.

[0049] In step S3, the biochar can be straw biochar with a mesh size of 80-150 meshes. The stirring intensity during mixing is 380-580 r / min. After the premix B and the biochar are evenly mixed, a mixture C can be obtained. In this embodiment, the biochar acts as an adsorbent.

[0050] The preparation process of straw biochar is as follows: after the crops are harvested, the crop straw should be collected as soon as possible, and the collected straw should be pretreated by high-temperature combustion, chemical treatment and other methods. After the pretreated straw is burned at high temperature, the remaining part is chemically treated to form biochar with specific structure and properties.

[0051] In step S4, NaOH is sodium hydroxide. When adding NaOH, a peristaltic pump is needed to add it dropwise. The stirring intensity during mixing is 280-480 r / min. After NaOH is mixed with mixture C, mixture D can be obtained. In this embodiment, sodium hydroxide plays the role of acid-base neutralization and pH adjustment, and the peristaltic pump plays the role of accurately conveying NaOH.

[0052] Step S5: After the mixture D is allowed to stand and is filtered, it is dried and ground and sieved by staff. The mesh size of the sieve is 30 to 60 meshes. The powdery substance after the sieve is recorded as E. In this embodiment, the sieve has the function of screening and filtering.

[0053] When using a tubular furnace in step S6, pyrolysis is performed in a N2 atmosphere. N2 is nitrogen. Nitrogen is a single substance formed by the nitrogen element. It is a colorless and odorless gas at room temperature and pressure. It can only react with hydrogen to generate ammonia under high temperature, high pressure and catalyst conditions. The pyrolysis temperature of the tubular furnace in step S6 is 300-500°C, and the pyrolysis time is 2-5h. In this embodiment, nitrogen plays a role in biogas replacement.

[0054] Embodiment 2

[0055] This example uses degradable microplastic PBS (polybutylene succinate) as the experimental object. Before the experiment, an absorbance-concentration standard curve of PBS is drawn to determine the concentration of microplastics in subsequent experiments.

[0056] The preparation method of magnetic biochar adsorbent specifically comprises the following steps:

[0057] S1. Mix uniformly according to the mass percentage of FeCl2·4H2O:FeCl3·6H2O=(3-7):(2-6), and the resulting mixture is recorded as A;

[0058] S2. The mixture A obtained in the first step is mixed with water in a mass ratio of water: A = (8 to 12): 1 to prepare a premix B;

[0059] S3. Add 2-6 g of straw biochar with a mesh size of 80-150 mesh to the premix B, stir at a stirring intensity of 380-580 r / min for 15-45 min to make the mixture uniform, and the resulting mixture is recorded as C;

[0060] S4. Add 3-7 mol / L NaOH dropwise to the mixture C using a peristaltic pump, adjust the pH to 8-11, stir at a stirring intensity of 280-480 r / min for 15-45 min to mix evenly, and the resulting mixture is recorded as D;

[0061] S5. The mixture D is allowed to stand for 18 to 26 hours, filtered, dried at 65 to 120°C, and ground through a 30 to 60 mesh sieve to obtain a powdery substance, which is recorded as E;

[0062] S6. The powdered substance E is pyrolyzed at 300-500° C. for 2-5 h in a tubular furnace with a nitrogen atmosphere to obtain the magnetic biochar adsorbent prepared by the present invention, which has high adsorption and removal performance and is easy to separate and recover microplastics.

[0063] The prepared magnetic biochar was added to 85-115 mg / L PBS at a certain concentration gradient within the range of 0.1-3 g / L, and placed in a constant temperature shaker for adsorption for 18-26 hours. Then, a magnet was used for batch adsorption, and the absorbance of the remaining solution was measured. The concentration of PBS was determined according to the standard curve, and the mass of PBS on the adsorbent was calculated. After experiments and calculations, with the increase in the dosage, their removal rate of PBS first showed an increasing trend, and then reached a maximum value when it reached 1.8-2.2 g / L, with a removal rate of more than 85%.

[0064] Embodiment 3

[0065] This example uses degradable microplastic PLA (polylactic acid) as the experimental object. Before the experiment, an absorbance-concentration standard curve of PLA is drawn to determine the concentration of microplastics in subsequent experiments.

[0066] The preparation method of magnetic biochar adsorbent specifically comprises the following steps:

[0067] S1. Mix uniformly according to the mass percentage of FeCl2·4H2O:FeCl3·6H2O=(3-7):(2-6), and the resulting mixture is recorded as A;

[0068] S2. The mixture A obtained in the first step is mixed with water in a mass ratio of water: A = (8 to 12): 1 to prepare a premix B;

[0069] S3. Add 2 to 6 g of straw biochar with a mesh size of 80 to 150 mesh to the premix B, stir at a stirring intensity of 380 to 580 r / min for 15 to 45 minutes to mix evenly, and the resulting mixture is recorded as C;

[0070] S4. Add 3-7 mol / L NaOH dropwise to the mixture C using a peristaltic pump, adjust the pH to 8-11, stir at a stirring intensity of 280-480 r / min for 15-45 min to mix evenly, and the resulting mixture is recorded as D;

[0071] S5. The mixture D is allowed to stand for 18 to 26 hours, filtered, dried at 65 to 120°C, and ground through a 30 to 60 mesh sieve to obtain a powdery substance, which is recorded as E;

[0072] S6. The powdered substance E is pyrolyzed at 300-500° C. for 2-5 h in a tubular furnace with a nitrogen atmosphere to obtain the magnetic biochar adsorbent prepared by the present invention, which has high adsorption and removal performance and is easy to separate and recover microplastics.

[0073] The obtained magnetic biochar was added to 85-115 mg / L PLA, placed in a constant temperature shaker for adsorption for 18-26 hours, and then a magnet was used for batch adsorption. The absorbance of the remaining solution was measured, the concentration of PLA was determined according to the standard curve, and the mass of PLA on the adsorbent was calculated. After calculation, the removal efficiency exceeded 98%.

[0074] The implementation principle of this embodiment is:

[0075] FeCl2·4H2O:FeCl3·6H2O=(3-7):(2-6) mass percentage was added to the interior of the experimental vessel and mixed evenly to form a mixture A. After mixing evenly, water was added to the interior of the experimental vessel at a ratio of A=(8-12):1 and stirred evenly again to form a premix B. At this time, 2-6 g of biochar was added to the interior of the experimental vessel and stirred for 15-45 minutes to mix evenly and blend with the premix B. The resulting mixture was recorded as C. NaOH with a concentration of 3-7 mol / L is added to the mixture, the pH value is adjusted to 8-11, and the mixture is stirred for 15-45 minutes to be evenly mixed. The resulting mixture is recorded as D. The mixture D is allowed to stand for 18-26 hours, filtered, and dried at 65-120°C. After grinding by the staff, the powdery substance obtained is sieved with a sieve and recorded as E. Finally, the powdery substance E is pyrolyzed in a tubular furnace at 300-500°C for 2-5 hours to obtain the magnetic biochar adsorbent prepared by the present invention with high adsorption and removal performance and easy separation and recovery of microplastics.

[0076] Compared with the prior art, the present invention has the following beneficial effects:

[0077] The present invention uses biochar made from waste straw in the agricultural production process as raw material. Compared with adsorbents such as silicone materials and polyamide fibers, the raw materials used in the present invention are low-cost, easy to obtain, simple in process, and have low requirements for production lines and equipment. At the same time, the present invention also has the effect of waste recycling. The magnetic biochar adsorbent prepared by the present invention is made of agricultural waste, which not only reduces waste emissions, but also utilizes waste resources. No secondary pollution is generated during the preparation and use process and it can be recovered by heat treatment, which further proves its environmental friendliness. The specific surface area of ​​the adsorbent prepared by the present invention is higher than 500m 2 / g, high adsorption and removal capacity for microplastics, high removal and adsorption efficiency. After adding the magnetic biochar prepared by the present invention to the mixed solution of degradable microplastics with a concentration of 85-115 mg / L, the removal rate is greater than 80%, and the removal efficiency is good. The adsorbent prepared by the present invention has a large magnetism. By using a vibrating sample magnetometer to analyze its magnetism, the saturation magnetization value exceeds 30emu / g and there is no residual magnetism and coercive force, indicating that it has superparamagnetism, ensuring effective magnetic separation performance, and thus achieving the purpose of separation from water. The present invention is the first to apply magnetic biochar to the adsorption and removal of small-sized (<2μm) degradable microplastics (PBS) in sewage, revealing the adsorption and removal performance and adsorption mechanism of magnetic biochar for small-sized degradable microplastics. The research results provide a theoretical basis for linking the pollution of degradable microplastics. The raw materials used in the magnetic biochar adsorbent prepared by the present invention are taken from waste straw, which is cheap and easy to obtain, effectively reducing the production cost, and thus greatly improving the market competitiveness of the product. At the same time, it strengthens the ecological environment governance of microplastics and ensures the ecological health of the water environment, which helps to achieve the goal of new pollutant governance.

[0078] The embodiments of this specific implementation method are all preferred embodiments of the patent of the present invention, and are not intended to limit the protection scope of the patent of the present invention. Therefore, all equivalent changes made based on the structure, shape, and principle of the patent of the present invention should be covered within the protection scope of the patent of the present invention.

Claims

1. Magnetic carbon material for efficient removal of degradable microplastics in sewage and its preparation, characterized by: The following steps are involved: S1. Mix uniformly according to the mass percentage of FeCl2·4H2O:FeCl3·6H2O=(3-7):(2-6), and the resulting mixture is recorded as A; S2. The mixture A obtained in the first step is stirred evenly with water to prepare a premix B; S3. Add 2 to 6 g of biochar to the premix B and stir for 15 to 45 min to mix them evenly. The resulting mixture is recorded as C. S4. Add NaOH with a concentration of 3 to 7 mol / L to the mixture C, adjust the pH thereof to 8 to 11, stir for 15 to 45 min to mix evenly, and the resulting mixture is recorded as D; S5. The mixture D is allowed to stand for 18 to 26 hours, filtered, and dried at 65 to 120° C. The powder obtained after grinding through a sieve is recorded as E; S6. Powdered substance E is pyrolyzed at 300-500° C. for 2-5 h using a tubular furnace to obtain the magnetic biochar adsorbent prepared by the present invention, which has high adsorption and removal performance and is easy to separate and recover microplastics.

2. The magnetic carbon material for efficient removal of degradable microplastics in sewage and its preparation method according to claim 1, characterized in that: In step S1, FeCl2 is ferrous chloride, 4H2O is ammonium molybdate tetrahydrate, FeCl3 is ferric chloride, and 6H2O is magnesium chloride hexahydrate. The mixture is added into the interior of the experimental vessel in a mass percentage of FeCl2·4H2O:FeCl3·6H2O=(3-7):(2-6), and mixed evenly to obtain a mixture A.

3. The magnetic carbon material for efficient removal of degradable microplastics in sewage and its preparation method according to claim 1, characterized in that: The mixing ratio of the mixture A and water in step S2 is: A=(8-12):

1. Water is added into the mixing vessel and fully mixed with the mixture A to obtain the premix B.

4. The magnetic carbon material for efficient removal of degradable microplastics in sewage and its preparation method according to claim 1, characterized in that: The biochar in step S3 may be straw biochar with a mesh size of 80 to 150 meshes, and the stirring intensity during mixing is 380 to 580 r / min. After the premix B and the biochar are evenly mixed, a mixture C can be obtained.

5. The magnetic carbon material for efficient removal of degradable microplastics in sewage and its preparation method according to claim 1, characterized in that: The straw biochar preparation process is as follows: after the crops are harvested, the crop straw should be collected as soon as possible, and the collected straw should be pretreated by high-temperature combustion, chemical treatment and other methods. After the pretreated straw is burned at high temperature, the remaining part is chemically treated to form biochar with specific structure and properties.

6. The magnetic carbon material for efficient removal of degradable microplastics in sewage and its preparation method according to claim 1, characterized in that: In step S4, NaOH is sodium hydroxide. When adding NaOH, a peristaltic pump is used to add it dropwise. The stirring intensity during mixing is 280-480 r / min. After NaOH is mixed with mixture C, mixture D can be obtained.

7. The magnetic carbon material for efficient removal of degradable microplastics in sewage and its preparation method according to claim 1, characterized in that: In step S5, after the mixture D is allowed to stand and is filtered, it is dried and ground and sieved by staff. The mesh size of the sieve is 30 to 60 meshes. The powdery substance after the sieve is recorded as E.

8. The magnetic carbon material for efficient removal of degradable microplastics in sewage and its preparation method according to claim 1, characterized in that: When the tubular furnace is used in step S6, pyrolysis is performed in a N2 atmosphere. N2 is nitrogen, which is a single substance formed by the nitrogen element. It is a colorless and odorless gas at room temperature and pressure. It can only react with hydrogen to generate ammonia under high temperature, high pressure and catalyst conditions.

9. The magnetic carbon material for efficient removal of degradable microplastics in sewage and its preparation method according to claim 1, characterized in that: The pyrolysis temperature of the tubular furnace in step S6 is 300-500° C., and the pyrolysis time is 2-5 hours.

Citation Information

Patent Citations

  • Method for treating dye wastewater through cooperation of adsorption and magnetization separation technologies

    CN110316898A

  • Magnetic nanocarbon, preparation method thereof and application of magnetic nanocarbon in removal of micro-plastics in water

    CN111514868A

  • Biochar adsorption catalytic material capable of being magnetically recycled as well as preparation method and application of biochar adsorption catalytic material

    CN112844385A

  • Preparation method of magnetic modified biochar and application of magnetic modified biochar to adsorption of micro-plastics

    CN117839628A

  • Efficient removal and green catalytic degradation method for microplastics in water body

    CN117902664A

Cited By

  • Bifunctional catalyst for coupling water-gas shift and plastic hydrogenolysis reaction as well as preparation method and application of bifunctional catalyst

    CN122032580A